The timing and other determinants of gas central heating adoption - Daire McCoy; John Curtis (The Economic and Social Research Institute (ESRI), 2016)
In order to better understand the potential for both policy and technological improvements to aid carbon abatement, long-term historical information on the time-path of transition from more traditional to cleaner fuels is useful. Knowing how this varies by socio-economic, demographic and geographic factors is also crucial in designing targeted policies. This research examines the timing and determinants of residential gas connections at area level within Ireland. We merge a unique dataset on gas network roll-out over time, with other geo-coded data and employ an instrumental variables technique in order to simultaneously model supply and demand. Results indicate a non-linear relationship between the proportion of households using gas as their primary means of central heating and the length of time the network has been in place in each area. Proximity to the gas network, peat bogs, and areas which have banned the consumption of bituminous coal also affect gas connections. Variations in socioeconomic and dwelling characteristics at area level can also help explain connections to the gas network.
Keywords: Q40; C31; C36; 330; Gas network; Residential heating; Spatial economics; Instrumental variables estimation